How useful is the evaluation of teaching? An exploratory study on students' beliefs - Jose-Maria Ernesto Garcia Garduno (Arizona State University, 2014)
The aim of the present paper was to explore student beliefs on teaching evaluation, their purposes, validity, and positive and negative aspects. One hundred sixty three college students of Social Sciences and Humanities majors of a Mexican public university participated in this study. Results point out that for students the evaluation of teaching has a summative purpose of control and supervision of classroom teaching. Students deem that evaluation of teaching lacks usefulness and student ratings of teaching are not a valid measure. The study concluded that policies on evaluation of teaching have not yielded expected results and that students' beliefs are similar to those findings reported by recent research that is critical of the use of student ratings to improve the quality of teaching. Results are discussed.